MECHANICAL PROPERTIES OF NATURAL FIBER COMPOSITE MADE OF INDONESIAN GROWN SISAL - Jauhar Fajrin (Universitas Lambung Mangkurat, 2016)
Sisal fiber is one of the most widely used natural fibers and is very easily to be cultivated. Sisal is considered to be indigenous to central and south America. According to FAO, nearly 4.5 million tons of sisal fiber is produced every year throughout the world. Brazil and Tanzania are the two main producing countries. Indonesia and Thailand are two of the South East Asian countries that also produces sisal. This paper presents a comprehensive experimental work on the fabrication and characterization of epoxy composite reinforced with Indonesian grown sisal. The sisal fiber was specifically grown in Lombok, Indonesia. The composite laminate was fabricated using vacuum bagging process. The characterization processes were conducted to evaluate the the mechanical properties which includes tensile, flexure, shear and compressive properties of such composites. The results showed that the mechanical properties of the examined sisal-epoxy composite in this study has a comparable properties with some of the previous reported studies. The epoxy composite reinforced with unidirectional oriented sisal (UOS) fiber has the tensile, flexural, shear and compressive stress of 40.25 MPa, 62.16 MPa, 23.26 MPa and 60.88 MPa, respectively. While the epoxy composite reinforced with randomly oriented sisal (ROS) fiber has the tensile, flexural, shear and compressive stress of 22.52 MPa, 51.5 MPa, 22.34 MPa and 49.12 MPa, respectively. The results have clearly shown that epoxy composite reinforced with unidirectional oriented sisal fiberhas a better mechanical properties than epoxy composite reinforced with randomly oriented sisal fiber.